Here's the question you clicked on:
davane
Imagine you are teaching a fellow student how to solve: 4 + 2(x - 1) = 5x - (x + 10) In your own words, explain the process for solving this equation. Please include your work at each step of the process along with the final answer
Remove the brackets both sides. That will give you 4+(2*x)-(2*1)=5x-(1*x)-(1*10) 4+2x-2=5x-x-10 When you simplify 2+2x=4x-10 Nw bring all terms containing x to one side. keeping the numbers in the other side. 2+10=4x-2x 12=2x Now divide both sides by 2 12/2=(2x)/2 6=x Is that clear?